Thermo-economic analysis of an integrated solar power generation system using nanofluids - Alashkar, Adnan (2017)
In this paper, a thermo-economic analysis of an Integrated Solar Regenerative Rankine Cycle (ISRRC) is performed. The ISRRC consists of a nanofluid-based Parabolic Trough Solar Collector (PTSC), and a Thermal Energy Storage System (TES) integrated with a Regenerative Rankine Cycle. The effect of dispersing metallic and non-metallic nanoparticles into conventional heating fluids on the output performance and cost of the ISRRC is studied for different volume fractions and for three modes of operation. The first mode assumes no storage, while the second and the third assume a storage system with a storage period of 7.5 h and 10 h respectively. For the modes of operation with the TES, the charging and discharging cycles are explained. The results show that the presence of the nanoparticles leads to an increase in the overall energy produced by the ISRRC for all modes of operation, causing a decrease in the Levelized Cost of Electricity (LEC), and an increase in the net savings of the ISRRC. After comparing the three modes of operation, it is established that the existence of a storage system leads to a higher power generation, and a lower LEC; however, the efficiency of the cycle drops. It is seen that the maximum increase in the annual energy output of the ISRRC caused by the addition of Cu nanoparticles to Syltherm 800 is approximately 3.1%, while the maximum increase in the net savings is about 2.4%.